A Comparative Study of TikTok as an Arabic Learning Medium to Improve Student Vocabulary at UIN STS Jambi and UIN Mataram - Hasnaida Azmiatik; Musli Musli; Yogia Prihartini; Dina Chabib Uluum; Mustar Mustar; Abdul Hakim Abdurrahman Husein (Ijaz Arabi Journal of Arabic Learning, 2026)
The purpose of this research is to examine how well students at UIN STS Jambi and UIN Mataram have learned Arabic language (mufradat) via the use of the TikTok app. The main focus of this research is to identify differences in the level of usefulness, students’ responses, and vocabulary improvement outcomes between the two institutions. The research employs a descriptive quantitative approach, using a Likert-scale questionnaire administered to 60 respondents (30 students from each university). The collected data were analyzed through descriptive statistics in the form of percentages and mean scores to examine the comparative results. The findings reveal a significant difference in effectiveness between the two universities. UIN STS Jambi obtained 90% in the very effective category, while UIN Mataram obtained 85% in the effective category. These results indicate that students at UIN STS Jambi utilize TikTok more consistently and purposefully for vocabulary learning, whereas students at UIN Mataram demonstrate positive yet less optimal outcomes due to more situational usage. This conclusion confirms that TikTok does not only provide a positive impact in general but also displays varying results based on institutional context, usage patterns, and learning environments. Therefore, TikTok is considered feasible and recommended as a technology-based learning medium, particularly for improving Arabic vocabulary mastery in Islamic higher education settings.